Impact of the Family Hope Program (PKH) on Household Expenditure in East Java, 2024 - Nurdiana, Elvika Nanda; Monika, Anugerah Karta (Politeknik Statistika STIS, 2025)
Poverty remains a development challenge in Indonesia, particularly in East Java, which contributes substantially to the national poverty rate. Household expenditure, which reflects a household’s ability to meet basic needs and maintain living standards, is widely used as a proxy for welfare and poverty. Assessing how social assistance programs influence expenditure is therefore crucial to understand their impact in improving welfare. The Family Hope Program (Program Keluarga Harapan/PKH), a conditional cash transfer initiative, aims to improve household welfare and reduce poverty. This study describes the characteristics of PKH recipients and evaluates the program’s impact on household expenditure as an indicator of welfare in East Java. This analysis uses data from the March 2024 Susenas survey on households that meet the PKH criteria, with separate analyses by household poverty levels. The Propensity Score Matching method was used to address selection bias resulting from non-random recipient selection. The results show that PKH recipients generally face limitations in housing, basic access, and socio-economic conditions. Overall, PKH has not increased total expenditures, but there has been an increase in food expenditures among extremely-poor households. Policy adjustments are needed to better align with the needs and characteristics of each group.